Maternal Health Practices and Beliefs Among Married Female Students in Colleges of Education in Anambra State, Nigeria - Nwankwo Nonyelum Stella; Nwankwo Chisom Cecilia (BIRCU, 2023)
This study examines the maternal health practices and beliefs among married female students in colleges of education in Anambra state, Nigeria. The study employed a descriptive survey design, and data were collected using a self-created questionnaire distributed electronically via email and social media channels. A total of 180 married female students from colleges of education in Anambra state participated in the study. The questionnaire consisted of three clusters: personal details, knowledge about maternal health practices, and maternal health beliefs. The data were analyzed using descriptive statistics, bivariate correlational analyses, and Pearson product moment correlations. The findings revealed that the majority of married female students in colleges of education practiced positive maternal health behaviors such as receiving antenatal care and planning to deliver in a health facility. They also held strong beliefs regarding the benefits of antenatal care for both the mother and child. However, there were some misconceptions, such as the belief that eating more food is necessary when pregnant. The study identified several factors influencing maternal health practices and beliefs, including educational level, marital status, and access to information. It also highlighted the importance of educational interventions to improve knowledge and promote healthy maternal behaviors among married female students. The results of this study have important educational implications for colleges of education in Anambra state. There is a need for targeted educational programs and interventions that address misconceptions and promote evidence-based maternal health practices among married female students. These programs should focus on improving knowledge, fostering positive attitudes, and enhancing access to healthcare services. By addressing these factors, colleges of education can contribute to the overall well-being of their students and future mothers, ultimately leading to improved maternal and child health outcomes in Anambra state, Nigeria